Motivational factors and mediating role of leadership on employee engagement in ready-made garments industry in Bangladesh - Hossan, Dalowar (2019)
Special attention has been devoted to the relationship between motivational factors and employee engagement (EE) over the past years. Based on the literature review it has been discovered that motivational factors have great effects on EE, although motivational factors have strong appeal in employee engagement, the evidence corroborating the links between intrinsic motivational factors (IMF), extrinsic motivational factors (EMF) and EE is lacking, especially in the ready-made garments (RMG) sectors in Bangladesh. Given this deficiency, the study aims to investigate the effects of intrinsic motivational factors IMF, EMF on EE. In addition, the mediating effect of transformational leadership style (TFL) and transactional leadership (TAL) style on these relationships will also be examined. The quantitative technique had been used in the study, SPSS is utilized to analyse the data collected from 387 of respondents from the RMG industry in Bangladesh. The findings show EMF have more positive relationship with employee engagement than intrinsic motivational factors. Again, transformational leadership is more positively related with employee engagement than transactional leadership among the employee of RMG industry in Bangladesh. Both types of leadership mediate the relationship between motivational factors and employee engagement partially. Therefore, it is crucial for the leaders to combine the leadership styles in their practices. It is also important to understand the facts about motivation in order to foster employee engagement. Future research could be conducted by exploring the practices which are most relevant to EE, which contingency factors influence the connection of intrinsic IMF, EMF and EE.